Dynamics Simulation of Multistage Planetary Gear Transmission System based on LMS Motion - Zhang Zhonggang; Fang Bin; Xu Ming (Jixie chuandong)
The two- stage planetary gear transmission system model is established based on LMS Virtual.Lab Motion platform. The dynamics simulation model is established in LMS with the two- stage planetary gear system coupled model and considering the problem of nonlinear vibration of gear system. The frequency domain load map and time domain load map of gear meshing force of the system are obtained by simulation that can be used for the research of vibration and noise later. The feasibility of gear system dynamics analysis with the help of virtual prototype is verified by comparing simulation data with theoretical calculations,and a new path for the research is provided.